Constitutively active β-catenin confers multi-lineage differentiation potential on lymphoid and myeloid progenitors - Baba, Yoshihiro (2005)
β-catenin mediated Wnt signaling may contribute to the self-renewal of hematopoietic stem cells and proliferation in some malignancies. We now show that expression of constitutively active β-catenin in normal lymphoid or myeloid progenitors generated uncommitted cells with multi-lineage differentiation potential. Inappropriate gene expression occurred in cells destined to produce either cell type and caused corresponding changes in their characteristics. For example, forced activation of β-catenin quickly increased C/EBPα while reducing EBF and Pax-5 in lymphoid progenitors that then generated myeloid cells. Inversely, EBF dramatically increased in transduced myeloid progenitors and lymphocytes were produced. The results indicate that ectopic activation of β-catenin de-stabilizes lineage fate decisions and confers some, but not all stem cell properties on committed progenitors.